Epidermal Mucus Extracts of three Freshwater Air-Breathing Fish Species against Gram Positive and Gram Negative Human Pathogenic Bacteria - Jameel, Farheen; Agarwal, Jyotsna; Waseem, Mohammad; Serajuddin, M. (Indian Journal of Fisheries, 2019)
Mucus layer from epidermal secretions of the fish act as a first line of defense between fish and pathogens in their environment. Fish skin mucus has been reported to prevent colonisation of pathogenic bacteria. The objective of the present study was to explore the antibacterial activity of epidermal mucus extracts from three freshwater air-breathing fish species (Clarias gariepinus, Heteropneustis fossilis and Channa punctatus) against human bacterial pathogens. The crude, acidic and organic extracts of skin mucus were prepared and tested for antibacterial activity by disc diffusion method against three Gram positive (Enterococcus faecalis, Staphylococcus aureus and Streptococcus pneumoniae) and 5 Gram negative (Escherichia coli, Salmonella typhi, Klebsiella pneumoniae, Vibrio inaba and Pseudomonas aeruginosa) bacteria. Out of 72 tests performed (nine types of mucus extracts against eight different bacterial strains), 59 tests showed antibacterial activity. The order of the level of antibacterial activity of the mucus of the three fish species observed in the present study was, C. gariepinus > C. punctatus > H. fossilis and the acidic extract of C. gariepinus showed the maximum antibacterial activity against Gram negative bacteria.